Dynamic air/liquid pockets for guiding microscale flow - Xu Hou (Nature Portfolio, 2018)
Fouling of solid surfaces is a problem when designing microchannel systems for applications such as bioassays and drug delivery. Here Hou et al. propose a way to overcome this issue by controlling fluid flow by means of an immiscible functional liquid partly infiltrated in a porous solid matrix.